2002
DOI: 10.1046/j.1365-294x.2002.01555.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differentiation of the dengue vector, Aedes aegypti (Ho Chi Minh City, Vietnam) using microsatellite markers

Abstract: Dengue haemorrhagic fever emerged in the 1950s and has become a major public health concern in most Asian countries. In Vietnam, little is known about the intraspecific variation of the vector and its consequences on vectorial capacity. Here we report the use of microsatellite markers to differentiate Aedes aegypti populations in Ho Chi Minh City, a typical, overcrowded Asian city. Six microsatellite loci, with 5-14 alleles per locus, were scored in 20 mosquito samples collected in 1998 in Ho Chi Minh City. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 28 publications
4
43
1
1
Order By: Relevance
“…Temporary breeding sites disappear and a population bottleneck may have led to a reduction of polymorphism. This same pattern was very marked in populations from Ho Chi Minh City (Huber et al, 2002).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Temporary breeding sites disappear and a population bottleneck may have led to a reduction of polymorphism. This same pattern was very marked in populations from Ho Chi Minh City (Huber et al, 2002).…”
Section: Discussionsupporting
confidence: 55%
“…aegypti in Cambodia underlines the low level of genetic differentiation compared to that detected in Thailand (Mousson et al, 2002) or from Vietnam (Tran et al, 1999;Huber et al, 2002).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The number of alleles per locus in the populations of O. taeniorhynchus analyzed had a range of 3 to 5, being relatively low in comparison with other population genetic studies carried out in mosquitoes with microsatellite markers; thus, for example, Huber et al (2002), established for A. aegypti a range of 4 to 12 alleles per locus; Scarpassa and Conn (2007) determined for A. darlingi a range of 5 to 25 alleles per locus; Mirabello et al (2008) showed for different populations of A. darlingi from Peru and Brazil, ranges of 5 to 11 and 6 to 22 alleles per locus, respectively. However, ranges of allele numbers per locus have been established that are similar to that of the present study, as reported by Mirabello et al (2008) using the same species but in other populations of the mosquito from Belize and Guatemala, where the range was 2 to 7 alleles per locus.…”
Section: Polymorphism Number Of Alleles Per Locus and Genetic Variabmentioning
confidence: 75%
“…aegypti populations within cities have been extensively studied in Southeast Asian cities of Cambodia, Vietnam and Thailand (Tran Khanh et al 1999, Huber et al 2002, Paupy et al 2004a, b, Bosio et al 2005. In general, samples from different neighbourhoods showed significant genetic differentiation.…”
mentioning
confidence: 99%